The use of e-commerce during COVID-19 pandemic towards revenue and volume of MSMEs sales - Mandasari , I.A. Cynthia Saisaria; Pratama , I Gede Surya (International research journal of management, IT and social sciences, 2020)
A large number of MSMEs in Denpasar City must be able to overcome the challenges caused by the COVID-19 virus and must be able to reach changes around it. Marketing communication must be done as well and as effectively as possible to potential customers. The use of online strategies with e-commerce media is currently the best solution for MSMEs. This is because promotion through online media is easier to reach consumers in terms of introducing or selling their products without having to meet face to face. E-commerce makes it easier for consumers and producers to make transactions. The purpose of this research is to examine the effect of e-commerce on the income and sales volume of MSMEs in Denpasar City. Targeting MSMEs as research respondents. The data collection technique used is a questionnaire technique with a sample of 100 MSME owners. The data obtained will be analyzed using a partial least square (PLS) based structural technique. The results of this study are expected to be able to contribute ideas to related parties, in this case, the community, government, and MSMEs players related to the effect of e-commerce on the income and sales volume of MSMEs.